A method for testing the crystallization rate of glass fiber

By heating and rapid cooling of the glass fiber sample, it can perform insulation measurement in the crystallization gradient furnace, which solves the problem of difficulty in measuring the crystallization growth rate of glass fiber in the prior art, and accurately measure the crystallization rate and improves the stability of the production process.

CN115508403BActive Publication Date: 2025-03-18CHONGQING POLYCOMP INT
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210881835.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-26
Publication Date
2025-03-18
Estimated Expiration
2042-07-26

AI Technical Summary

Technical Problem

The prior art is difficult to accurately measure the crystallization growth rate of glass fibers, which affects the stability of glass formulation development and production process.

Method used

By heating the glass fiber sample, it is melted and homogenized, then quickly cooled, so that it automatically explodes into glass blocks, placed in a crystallization gradient furnace for insulation measurement, observe the length of the glass crystallization area at different time points, and construct a curve chart to obtain the crystallization rate.

Benefits of technology

Accurate measurement of the crystallization rate of glass fibers is achieved, and the impact of crystallization of glass can be understood in a timely manner, and the stability of glass formula development and production process is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115508403B_ABST
    Figure CN115508403B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for testing the crystallization rate of glass fiber, comprising the following steps: heating a glass fiber sample to be tested to melt it; rapidly cooling the molten glass fiber sample to automatically explode into a plurality of glass blocks; placing the plurality of glass blocks on a carrier; placing the carrier in a crystallization gradient furnace; keeping the plurality of glass blocks warm in the crystallization gradient furnace for t1, t2, t3, t4, t5, t6, t7, t8, t9, t10, t11, t12, t13, t14, t15, t16, t17, t18, t19, t20, t21, t22, t23, t24, t25, t26, t27, t28, t29, t30, t31, t32, t33, t34, t35 x‑1 ,t x ,t x+1 ···t n After the fiber is taken out, the length of the glass crystallization region corresponding to each time point of the removal is measured, and a curve diagram of the glass crystallization region length and time is constructed to obtain the glass fiber crystallization rate, t x‑1 ,t x ,t x+1 At the three time points, the length of the glass crystallization area is basically the same, and the glass crystallization area is the area where the glass loses its transparency. This method can simply, intuitively and quickly test the crystallization rate of glass fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of glass fiber performance testing, and in particular to a method for testing the crystallization rate of glass fibers. Background Art

[0002] Glass fiber is an inorganic material with excellent performance. It is non-toxic, heat-resistant, corrosion-resistant, has high mechanical strength and good electrical insulation. It is widely used in many fields such as aviation, automobiles, rail transportation, electronic appliances, chemicals, new energy, and construction. However, the production of glass fiber is a complex project involving multiple disciplines such as mineralogy crystallography, silicate physical chemistry, high-temperature fluid mechanics, thermodynamics, and automatic control. Especially for the production of high-performance glass fiber, it has strict requirements on glass formula design, kiln melting quality, and wire drawing technology. Among them, an important factor affecting the stability of high-performance glass fiber production is the problem of glass crystallization. We also found in actual production that poor wire drawing operation status is mostly caused by glass crystallization problems. Therefore, it is of great significance to simply, quickly and accurately evaluate the high-temperature crystallization state and crystallization rate of glass fiber during glass formula development and glass fiber production.

[0003] At present, the main methods for detecting the crystallization temperature of glass fiber in the industry are crystallization gradient furnace test and differential thermal analysis, but these two methods are mainly used to test the crystallization temperature of glass. There is currently no suitable method for measuring the crystallization growth rate of glass.

[0004] Therefore, how to provide a method for testing the crystallization rate of glass fiber has become a technical problem that technicians in this field urgently need to solve. Summary of the invention

[0005] To achieve the above object, the present invention provides a method for testing the crystallization rate of glass fiber, comprising the following steps:

[0006] Step (1): heating the glass fiber sample to be tested to melt and homogenize it into a liquid state;

[0007] Step (2): rapidly cooling the glass fiber sample that has been melted and homogenized into a liquid state, wherein the rapid cooling prevents crystallization of the glass fiber sample during the cooling process, and the cooling process causes the glass fiber sample to automatically explode into a plurality of glass blocks;

[0008] Step (3): placing the plurality of glass blocks on a carrier having a length direction, and laying the plurality of glass blocks on the carrier at intervals along the length direction;

[0009] Step (4): placing the carrier in a crystallization gradient furnace that has been heated to a set temperature, wherein the temperature of the low temperature end of the crystallization gradient furnace is T1, and the temperature of the high temperature end is T2, one end of the carrier along its length direction is placed corresponding to the low temperature end, and the other end of the carrier along its length direction is placed corresponding to the high temperature end, and the crystallization temperature of the glass fiber sample to be tested is between T1 and T2;

[0010] Step (5): Keep the glass blocks in the crystallization gradient furnace for t1, t2, t x-1 ,t x ,t x+1 ···t n After the fiber is taken out, the length of the glass crystallization region corresponding to each time point of the removal is measured, and a curve diagram of the glass crystallization region length and time is constructed to obtain the glass fiber crystallization rate, t x-1 ,t x ,t x+1 At three time points, the length of the glass crystallization region is substantially the same, and the glass crystallization region is the region where the glass loses its transparency.

[0011] Preferably, in step (1), the glass fiber sample to be tested is placed in a platinum crucible, and then placed in a muffle furnace heated to 1300-1600° C. and kept warm for 2-4 hours to melt and homogenize the glass fiber sample to be tested.

[0012] Preferably, the muffle furnace is heated to 1450°C.

[0013] Preferably, in the step (2), the platinum crucible carrying the molten homogenized glass fiber sample is placed in cold water for rapid cooling, so that the temperature of the glass fiber sample is cooled to room temperature within 1 minute.

[0014] Preferably, between step (2) and step (3), the following steps are further included:

[0015] The glass blocks are broken into glass blocks with a diameter less than 5 mm, cleaned, and then dried naturally or in an oven.

[0016] Preferably, T1 is any temperature in the range of 900-1100°C, and T2 is any temperature in the range of 1150-1350°C.

[0017] Preferably, T1 is 1000°C and T2 is 1250°C.

[0018] Preferably, in step (5), the insulation time points are 10 min, 30 min, 60 min, 90 min and 120 min respectively.

[0019] Preferably, the glass fiber sample to be tested is a sample of ECR ​​glass or a sample of R-grade glass.

[0020] The method for testing the crystallization rate of glass fiber provided by the present invention has the following technical effects:

[0021] The implementation of steps (1) and (2), that is, first heating the glass fiber sample to make it completely melt and homogenize into a liquid state, and then rapidly cooling it, can make it cool down quickly and solidify quickly without crystallization, that is, the later observation of crystal growth is observed from scratch, which ensures the accuracy of the crystallization rate detection; and by observing the length of the glass crystallization area at different time points, and then constructing a curve graph of it and time, for this reason, through the curve graph, the glass fiber crystallization rate at any time point can be obtained, which is of great significance for timely understanding the impact of glass crystallization during glass formula development and glass fiber production. And by directly observing the area where the glass loses transparency, the length of the glass crystallization area can be measured, which is very intuitive and simple.

[0022] Preferably, the glass fiber sample to be tested is placed in a muffle furnace heated to 1300-1600° C. and kept warm for 2-4 hours to melt and homogenize the glass fiber sample; this temperature limit is applicable to the melting of most glasses.

[0023] Preferably, cold water is selected as the cooling medium, which is low in cost and easy to implement.

[0024] Preferably, several glass blocks are broken into glass blocks with a diameter less than 5 mm. The smaller the diameter, the easier it is to melt and the faster and easier it is to observe the crystallization phenomenon at a later stage. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A curve diagram of the length of the glass crystallization region and time of the ECR glass sample;

[0026] Figure 2 The graph is a graph of the length of the glass crystallization region versus time for a sample of R-grade glass. DETAILED DESCRIPTION

[0027] like Figure 1 As shown in 2, Figure 1 A curve diagram of the length of the glass crystallization region and time of the ECR glass sample; Figure 2 The graph is a graph of the length of the glass crystallization region versus time for a sample of R-grade glass.

[0028] The present invention provides a method for testing the crystallization rate of glass fiber, comprising the following steps:

[0029] Step (1): heating the glass fiber sample to be tested to melt and homogenize it into a liquid state;

[0030] Step (2): rapidly cooling the glass fiber sample that has been melted and homogenized into a liquid state, wherein the rapid cooling prevents crystallization of the glass fiber sample during the cooling process, and the cooling process causes the glass fiber sample to automatically explode into a plurality of glass blocks;

[0031] Step (3): placing the plurality of glass blocks on a carrier having a length direction, and laying the plurality of glass blocks on the carrier at intervals along the length direction;

[0032] Step (4): placing the carrier in a crystallization gradient furnace that has been heated to a set temperature, wherein the temperature of the low temperature end of the crystallization gradient furnace is T1, and the temperature of the high temperature end is T2, one end of the carrier along its length direction is placed corresponding to the low temperature end, and the other end of the carrier along its length direction is placed corresponding to the high temperature end, and the crystallization temperature of the glass fiber sample to be tested is between T1 and T2;

[0033] Step (5): Keep the glass blocks in the crystallization gradient furnace for t1, t2, t x-1 ,t x ,t x+1 ···t n After the fiber is taken out, the length of the glass crystallization region corresponding to each time point of the removal is measured, and a curve diagram of the glass crystallization region length and time is constructed to obtain the glass fiber crystallization rate, t x-1 ,t x ,t x+1 At three time points, the length of the glass crystallization region is substantially the same, and the glass crystallization region is the region where the glass loses its transparency.

[0034] The implementation of steps (1) and (2), that is, first heating the glass fiber sample to make it completely melt and homogenize into a liquid state, and then rapidly cooling it, can make it cool down quickly and solidify quickly without crystallization, that is, the later observation of crystal growth is observed from scratch, which ensures the accuracy of the crystallization rate detection; and by observing the length of the glass crystallization area at different time points, and then constructing a curve graph of it and time, for this reason, through the curve graph, the glass fiber crystallization rate at any time point can be obtained, which is of great significance for timely understanding the impact of glass crystallization during glass formula development and glass fiber production. And by directly observing the area where the glass loses transparency, the length of the glass crystallization area can be measured, which is very intuitive and simple.

[0035] Wherein, in step (1), the glass fiber sample to be tested is placed in a platinum crucible, and then placed in a muffle furnace heated to 1300-1600° C. and kept warm for 2-4 hours to melt and homogenize the glass fiber sample to be tested.

[0036] The glass fiber sample to be tested is placed in a muffle furnace heated to 1300-1600° C. and kept warm for 2-4 hours to allow the glass fiber sample to be melted and homogenized. This temperature limit is applicable to the melting of most glasses.

[0037] Furthermore, the temperature of the muffle furnace was raised to 1450° C., which was a temperature considered in consideration of cost and handling of most glass samples.

[0038] Wherein, in step (2), the platinum crucible carrying the molten homogenized glass fiber sample is placed in cold water for rapid cooling, so that the temperature of the glass fiber sample is cooled to room temperature within 1 minute.

[0039] Choosing cold water as the cooling medium is low-cost and easy to implement.

[0040] Furthermore, between step (2) and step (3), the following steps are also included:

[0041] The glass blocks are broken into glass blocks with a diameter less than 5 mm, cleaned, and then dried naturally or in an oven.

[0042] Several glass blocks are broken into glass blocks with a diameter less than 5 mm. The smaller the diameter, the easier it is to melt and the faster and easier it is to observe the crystallization phenomenon at a later stage.

[0043] Wherein, T1 is any temperature between 900-1100°C, and T2 is any temperature between 1150-1350°C.

[0044] Specifically, T1 is 1000°C and T2 is 1250°C.

[0045] In step (5), the insulation time points are 10 min, 30 min, 60 min, 90 min and 120 min respectively.

[0046] The following are two specific implementation methods:

[0047] The first specific implementation method:

[0048] 1. Place an ECR glass sample in a platinum crucible and place it in a muffle furnace heated to 1450°C for 2 hours to fully melt and homogenize the glass sample;

[0049] 2. Take out the melted glass sample from the muffle furnace and quickly put it into cold water to make the glass liquid cool rapidly and automatically explode into small pieces;

[0050] 3. Take out the cooled glass block, break it into glass blocks with a diameter less than 5mm, clean it, and place it to dry naturally for one day;

[0051] 4. Evenly spread the dried glass blocks in a boat-shaped platinum crucible, and then send them together into a crystallization gradient furnace that has been heated to the set temperature. The high and low temperature ends of the crystallization gradient furnace are set to 1000°C and 1250°C respectively;

[0052] 5. The samples were taken out after being kept warm for 10min, 30min, 60min, 90min and 120min respectively, and the length of the glass crystallization area of ​​the samples at different time periods was measured to construct a curve of the length of the glass crystallization area and time. Figure 1 shown.

[0053] The second specific implementation method:

[0054] 1. Place an R-grade glass fiber sample in a platinum crucible and place it in a muffle furnace heated to 1450°C for 2 hours to fully melt and homogenize the glass sample;

[0055] 2. Take out the melted glass sample from the muffle furnace and quickly put it into cold water to make the glass liquid cool rapidly and automatically explode into small pieces;

[0056] 3. Take out the cooled glass block and break it into broken glass blocks with a diameter of less than 5mm. After cleaning, place it for one day to dry naturally.

[0057] 4. Evenly spread the dried broken glass pieces in a boat-shaped platinum crucible, and then send them together into a crystallization gradient furnace that has been heated to the set temperature. The high and low temperature ends of the crystallization gradient furnace are set to 1000°C and 1250°C respectively;

[0058] 5. The samples were taken out after being kept warm for 10min, 30min, 60min, 90min and 120min respectively, and the length of the glass crystallization area of ​​the samples at different time periods was measured to construct a curve of the length of the glass crystallization area and time. Figure 2 shown.

[0059] And through this method, the crystallization growth rate of glasses with different compositions at high temperatures can be quickly measured.

Claims

1. A method for testing the crystallization rate of glass fiber, characterized in that: The steps include: Step (1): heating the glass fiber sample to be tested to melt and homogenize it into a liquid state; Step (2): rapidly cooling the glass fiber sample that has been melted and homogenized into a liquid state, wherein the rapid cooling prevents crystallization of the glass fiber sample during the cooling process, and the cooling process causes the glass fiber sample to automatically explode into a plurality of glass blocks; Step (3): placing the plurality of glass blocks on a carrier having a length direction, and laying the plurality of glass blocks on the carrier at intervals along the length direction; Step (4): placing the carrier in a crystallization gradient furnace that has been heated to a set temperature, wherein the temperature of the low temperature end of the crystallization gradient furnace is T1, and the temperature of the high temperature end is T2, one end of the carrier along its length direction is placed corresponding to the low temperature end, and the other end of the carrier along its length direction is placed corresponding to the high temperature end, and the crystallization temperature of the glass fiber sample to be tested is between T1 and T2; Step (5): Keep the glass blocks in the crystallization gradient furnace for t1, t2, t x-1 ,t x ,t x+1 ···t n After the fiber is taken out, the length of the glass crystallization region corresponding to each time point of the removal is measured, and a curve diagram of the glass crystallization region length and time is constructed to obtain the glass fiber crystallization rate, t x-1 ,t x ,t x+1 At three time points, the length of the glass crystallization region is substantially the same, and the glass crystallization region is the region where the glass loses its transparency.

2. The method for testing the crystallization rate of glass fiber according to claim 1, wherein: In the step (1), the glass fiber sample to be tested is placed in a platinum crucible, and then placed in a muffle furnace heated to 1300-1600° C. and kept warm for 2-4 hours to melt and homogenize the glass fiber sample to be tested.

3. The method for testing the crystallization rate of glass fiber according to claim 2, wherein: The muffle furnace was heated to 1450°C.

4. The method for testing the crystallization rate of glass fiber according to claim 2, wherein: In the step (2), the platinum crucible carrying the molten homogenized glass fiber sample is placed in cold water for rapid cooling, so that the temperature of the glass fiber sample is cooled to room temperature within 1 minute.

5. The method for testing the crystallization rate of glass fiber according to claim 4, characterized in that: Between step (2) and step (3), the method further includes: The glass blocks are broken into glass blocks with a diameter less than 5 mm, cleaned, and then dried naturally or in an oven.

6. The method for testing the crystallization rate of glass fiber according to claim 1, characterized in that: T1 is any temperature between 900-1100°C, and T2 is any temperature between 1150-1350°C.

7. The method for testing the crystallization rate of glass fiber according to claim 6, characterized in that: T1 is 1000℃ and T2 is 1250℃.

8. The method for testing the crystallization rate of glass fiber according to claim 1, characterized in that: In the step (5), the insulation time points are 10 min, 30 min, 60 min, 90 min and 120 min respectively.

9. The method for testing the crystallization rate of glass fiber according to claim 1, characterized in that: The glass fiber sample to be tested is a sample of ECR ​​glass or a sample of R-grade glass.

Citation Information

Patent Citations

  • Crystallization method and crystallization apparatus for same

    CN105477897A

  • Glass liquidus temperature determining method

    CN107037073A